Evaluation of Patient Benefits from the Superficial Circumflex Iliac Artery Perforator Flap in Elderly Patients - Hongmin Luo; Huining Bian; Zuan Liu; Chuanwei Sun; Hanhua Li; Lianghua Ma; Xiaoyan Wang; Zhifeng Huang; Xu Mu; Shenghua Chen; Yuyang Han; Lin Zhang; et al. (Bioengineering)
Background: The superficial circumflex iliac artery perforator (SCIP) flap is widely recognized for its reliability and minimal donor site morbidity in reconstructive surgery. However, its safety and efficacy in elderly patients—a growing demographic with increased comorbidities—remain less understood. This study aims to evaluate the clinical outcomes of the SCIP flap in elderly patients compared to younger patients, focusing on flap survival, complications, and recovery. Methods: In this retrospective cohort study, conducted at Guangdong Provincial People’s Hospital, from 28 August 2019 to 7 June 2024, we included 37 patients who underwent SCIP flap procedures for reconstruction. Patients were divided into two groups: younger (15–59 years) and elderly (≥60 years). Key variables analyzed included demographics, comorbidities, flap characteristics, recipient sites, arterial sources, and surgical outcomes. Univariate analysis and ROC curve analysis were used to explore the impact of age on flap survival and complications. Results: The cohort consisted of 28 younger and 9 elderly patients. Vascular disease was significantly more prevalent in the elderly group (88.9% vs. 21.4%, p = 0.001), and abnormalities in the CTA results indicate that the elderly cohort exhibited a 29-fold increased odds of vascular disease compared to younger patients (OR = 29.17, 95% CI: 4.82–176.40, p = 0.001). However, no significant differences were found between the groups in terms of flap area, recipient sites, or arterial sources. Hospital stay duration and flap survival rates were comparable across both age groups, with no cases of total flap loss reported. While systemic complications were somewhat higher in the elderly group, this difference did not reach statistical significance. The ROC analysis (AUC = 0.52) indicates that age alone is not a significant predictor of flap survival. Conclusions: The SCIP flap is a safe and effective reconstructive option for elderly patients, despite a higher incidence of vascular disease. Flap survival and postoperative recovery were favorable, indicating that the procedure is viable for older patients. These findings support the continued use of SCIP flaps in aging populations, emphasizing the need for individualized surgical approaches to optimize patient outcomes.